Advances in nanomaterials for promoting bone tissue regeneration by reducing reactive oxygen species levels - LU Jiayi; LIU Jinzhe; GUO Shangchun; TAO Shicong (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Reactive oxygen species (ROS) are common products of bone tissue injury. If ROS cannot be removed in time, oxidative stress will be induced in the cells, which will have a negative effect on the regeneration of bone tissue. In recent years, with the deepening of research, nanomaterials capable of reducing ROS levels have shown increasing potential in promoting bone tissue regeneration. Currently, nanomaterials applied to reduce ROS levels mainly include those with surface modifications and microstructural designs, dopant-modified inorganic materials, functionalized polymeric materials and hydrogels, and nano-enzymatic materials. However, the clinical application of these nanomaterials is still limited due to their potential cytotoxicity and the lack of sufficient clinical trials. This literature review summarises the research on the use of nanomaterials to reduce ROS levels to promote bone regeneration and provides ideas for the future design and development of novel nanomaterials in this field.